Production of a medicine based on aspirine in a capsulated form - A. Sh. Zainullina; D. S. Jarylgapova (Алматы технологиялық университетінің хабаршысы, 2021)
The article is devoted to the development of technology for obtaining a drug based on aspirin and paracetamol in the form of capsules. Marketing analysis has shown the relevance of the development of medicinal preparations in the form of capsules in Kazakhstan. The main physical, chemical and technological properties of the substance samples were studied. The quality indicators of the initial raw material and the finished product are determined. Technological calculations were performed.